Progress towards elimination of onchocerciasis transmission in Mali: A "pre-stop MDA" survey in 18 transmission zones. - Housseini Dolo; Michel Emmanuel Coulibaly; Moussa Sow; Yaya Ibrahim Coulibaly; Mama Doumbia; Moussa Sangare; Abdoul Sanogo; Benoit Dembele; Boubacar Guindo; Mamadou Coulibaly; Modibo Keita; Lamine Soumaoro; et al. (Public Library of Science (PLoS), 2023)
Background Onchocerciasis control activities in Mali began in 1975 with vector larviciding carried out by the Onchocerciasis Control Programme (OCP), followed by the distribution of ivermectin from 1998 until the closure of the OCP in 2002. At that time, epidemiological evaluations, using skin snip microscopy and O-150 pool screening PCR in black flies, indicated that the disease had been largely controlled as a public health problem. Ivermectin distribution was nevertheless continued after 2002 in 34 of the 75 health districts in Mali as these were known to still be meso- or hyper-endemic for onchocerciasis. In addition, the onchocerciasis sites known to be hypo-endemic for onchocerciasis benefited from the distribution of ivermectin treatment as part of the mass drug administration (MDA) program for lymphatic filariasis. Various entomological and epidemiological evaluations have now indicated that Mali may have achieved successful interruption of onchocerciasis transmission. Methods A series of cross-sectional surveys to update vector breeding sites throughout the endemic areas, followed by a pre-stop ivermectin mass drug administration (Pre-stop MDA) survey, were undertaken in 2019-2020. Based on breeding site findings, historical epidemiological assessments, and vector collection site maps, 18 operational transmission zones (OTZ) were delineated within which a total of 104 first line villages were selected for evaluation. Dried blood spots (DBS) samples were collected from 10,400 children (5-9 years old) from these 104 first line villages and processed for the presence of OV16 antibody using a lab-based rapid diagnostic test. Results Within the 544 Simulium damnosum s.l. breeding sites visited in all five endemic onchocerciasis endemic regions of Mali 18.01% (98/544) were seen to be active with the presence of at least one stage of S. damnosum. The overall prevalence of OV16 positive children was 0.45% (47/10,400). However, two hotspots were identified: 2.60% (13/500) seroprevalence in the OTZ number 5 in Kayes Region and 1.40% (7/500) in the OTZ number 1 of Sikasso Region. Conclusion These data show that onchocerciasis prevalence in the five endemic regions has declined to levels that indicate that Stop-MDA surveys should be now carried out in most of the OTZ except for one in the Kayes Region. This latter site will need additional ivermectin treatment before reevaluation, and an OTZ in the Sikasso Region requires revaluation before possibly reinitiating MDA.